1995
DOI: 10.1111/j.1432-1033.1995.tb20854.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sulfakinins of the Blowfly Calliphora Vomitoria. Peptide Isolation, Gene Cloning and Expression Studies

Abstract: The nonapeptide, Phe-Asp-Asp-Tyr(SO3)-Gly-His-Met-Arg-Phe-NH2 was isolated from heads of the blowfly Calliphora vomitoria. Designated callisulfakinin I, the peptide is identical to the earlier known drosulfakinin I of Drosophila melanogaster and to neosulfakinin I of Neobellieria bullata. It belongs to the sulfakinin family, all known members of which (from flies, cockroaches and locusts) have the C-terminal heptapeptide sequence Asp-Tyr(SO3)-Gly-His-Met-Arg-Phe-NH2. The callisulfakinin gene of C. vomitoria wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…Sulfakinins have been identified in various insects including the cockroaches Leucophaea maderae 11,12 and Periplaneta americana, 13 the locust Locusta migratoria 14 and the flies Neobellieria bullata 15 and Calliphora vomitoria. 16 Similar to CCK in vertebrates, sulfakinins reduce food intake in locusts and stimulate contraction in visceral muscles. 17 CCK-like peptides and insect sulfakinins share a sulfated tyrosine residue, which is essential for their activity.…”
Section: The Sulfakinin Precursormentioning
confidence: 99%
“…Sulfakinins have been identified in various insects including the cockroaches Leucophaea maderae 11,12 and Periplaneta americana, 13 the locust Locusta migratoria 14 and the flies Neobellieria bullata 15 and Calliphora vomitoria. 16 Similar to CCK in vertebrates, sulfakinins reduce food intake in locusts and stimulate contraction in visceral muscles. 17 CCK-like peptides and insect sulfakinins share a sulfated tyrosine residue, which is essential for their activity.…”
Section: The Sulfakinin Precursormentioning
confidence: 99%
“…translated nucleotide sequence versus protein sequence (Altschul et al, 1997)] and annotated accordingly. A single EST (NCBI accession number CN952349) with significant homology to a sulfakinin precursor from the blowfly Calliphora vomitoria (NCBI accession number Q7M3V5) (Duve et al, 1995) was identified during this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…translated nucleotide sequence versus protein sequence), a H. americanus EST (accession number CN952349) with homology to blowfly C. vomitoria prepro-sulfakinin (NCBI accession number Q7M3V5) (Duve et al, 1995) was identified. Using a combination of vector-and insert-specific forward-and reverse-sequencing primers (Table·2), a 1523 base pair (bp), putative full-length cDNA was sequenced (NCBI accession number EF418605).…”
Section: Nucleotide Sequence Of a Putative Homarus Americanusmentioning
confidence: 99%
See 2 more Smart Citations